Analysis Of Advertising Strategies On Teh Kota Sales Growth: A Sharia Economic Perspective - Moh Ivan Maulidi; Musthafa Syukur (International Journal of Management and Business Economics, 2026)
This study aims to analyze the advertising strategies implemented by Teh Kota in increasing sales from the perspective of Sharia economics in Probolinggo Regency. This study offers novelty by integrating advertising strategy analysis with Islamic economic principles in the context of local beverage MSMEs. The research employed a qualitative phenomenological approach through observation, interviews, and documentation involving business owners, employees, distributors, and consumers of Teh Kota. The findings indicate that Teh Kota utilized several advertising strategies, including social media promotion, banners, price promotions, and word-of-mouth marketing to attract consumer interest and expand market reach. Sales turnover increased by approximately 41.36% after promotional intensification in March 2026. From the perspective of Sharia economics, the promotional strategies generally reflected the principles of shiddiq, amanah, tabligh, and fathanah, although several aspects of digital promotion still require improvement. The study concludes that integrating ethical Islamic values into advertising strategies contributes to strengthening consumer trust and supporting sustainable local business development.